ESG and Firm Performance in Developing Countries: Evidence From ASEAN - Makhdalena Makhdalena; Desi Zulvina; Yani Zulvina; Rizky Windar Amelia; Aditya Pandu Wicaksono (ETIKONOMI, 2023)
Several studies primarily investigate the influence of environmental, social, and governance on firm performance in a developed country where markets have matured, and investors are aware of corporate social responsibility activities. Therefore, studies in developing countries are still rare and mixed. This study examines the effect of Environmental, Social, and Governance (ESG) information on firm performance in ASEAN developing countries. We observed companies in ASEAN developing countries (Indonesia, Malaysia, Philippines, Thailand, and Vietnam) during 2010-2020. The information on ESG score and ROA as a proxy for firm performance measures ESG. Regression test results showed that ESG has a positive effect on firm performance. We also found that three components of ESG, environmental, Social, and Governance, positively affect firm performance. Robustness test results showed that overall ESG information, environmental information, and social initiatives affect the firm’s market performance (Tobin’s Q). Research originality in this study proves that developing countries have a positive effect between ESG disclosure and company performance. ESG, in the long term, would build effective governance and increase shareholder value. The research implication is to suggest a company has ESG information due to empirical testing that ESG information enhances a firm operational and market performance.JEL Classification: G30, Q56, Q50How to Cite:Makhdalena., Zulvina, D., Zulvina, Y., Amelia, R. W., & Wicaksono, A. P. (2023). Environmental, Social, Governance, and Firm Performance in Developing Countries: Evidence from Southeast Asian. Etikonomi, 22(1), 65–78. https://doi.org/10.15408/etk.v22i1.25271.